TINJAUAN GANGGUAN FREKUENSI RADIO TOWER DAN GROUND CONTROLLER TERHADAP PELAYANAN LALU LINTAS PENERBANGAN DI PERUM LPPNPI CABANG SURABAYA - Arnaz Olieve; Mariska Novelia Adelaide; Ariyono Setiawan (Approach : Jurnal Teknologi Penerbangan, 2019)
Air traffic services are services provided with the aim of preventing collisions between aircraft, preventing collisions between aircraft on the manoeuvring area and obstruction on that area and expedite and maintain an orderly flow of air traffic. Communication is the most important tool in achieving the objectives of air traffic services. Especially communication is carried out 2 directions between ground to air and air to ground (two way communication) by Air Traffic Controller officers and pilots. The purpose of this study is to determine interference with Tower and Ground Controllers radio frequency in relation to the provision of air traffic services at Perum LPPNPI Branch of Surabaya. The method used in this study is the method of observation, interviews, dokumentation, then analyzed descriptively qualitatively using the gap analysis method, and literature review. The results of the study show that there is a need for mitigation in dealing with radio frequency interference by making a flowchart to handle radio frequency interference, maintenance of communication equipment and socialization to the public regarding the prohibition on the use of frequencies that radiate on the flight frequency band.